2012
DOI: 10.1007/s10643-012-0534-9
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Alphabet Knowledge Instruction: Research Implications and Practical Strategies for Early Childhood Educators

Abstract: Alphabet knowledge is consistently recognized as the strongest, most durable predictor of later literacy achievement. Recent research offers practical implications for increased effectiveness of teaching alphabet knowledge to young children. In this article, we outline Enhanced Alphabet Knowledge instruction (EAK), a method of practical instruction that early childhood teachers can use to organize, plan, and teach the essential skills of alphabet knowledge. EAK emphasizes identifying the letter name and sound,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
46
0
12

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 30 publications
6
46
0
12
Order By: Relevance
“…That is, these researchers have demonstrated that students, regardless of disability status or background, can make gains when provided explicit skill instruction. Yet, current practices associated with alphabet instruction (a) vary widely (Justice, Pence, Bowles, & Wiggins, 2006); (b) often employ a one-letter-per-week approacha common, yet flawed practice (Jones et al, 2013); and (c) can be insufficient to meet the needs of students most at risk for reading failure (Piasta & Wagner, 2010). Thus, although studies have demonstrated the capacity of explicit, letter-sound instruction to result in gains in student learning, in order for strong instruction to occur at the K-12 level, teachers need to possess the knowledge and skills necessary for teaching phoneme-grapheme correspondence.…”
Section: Importance Of Phoneme-grapheme Correspondence Knowledgementioning
confidence: 99%
“…That is, these researchers have demonstrated that students, regardless of disability status or background, can make gains when provided explicit skill instruction. Yet, current practices associated with alphabet instruction (a) vary widely (Justice, Pence, Bowles, & Wiggins, 2006); (b) often employ a one-letter-per-week approacha common, yet flawed practice (Jones et al, 2013); and (c) can be insufficient to meet the needs of students most at risk for reading failure (Piasta & Wagner, 2010). Thus, although studies have demonstrated the capacity of explicit, letter-sound instruction to result in gains in student learning, in order for strong instruction to occur at the K-12 level, teachers need to possess the knowledge and skills necessary for teaching phoneme-grapheme correspondence.…”
Section: Importance Of Phoneme-grapheme Correspondence Knowledgementioning
confidence: 99%
“…Piasta and Wagner () found that the most effective alphabet knowledge instruction is multicomponential, meaning that lessons should include learning activities that require letter recognition, naming, associating the symbol with a sound, writing, discriminating the letter to be taught from other letters, and categorizing letters into upper‐ and lowercase, to name a few. Jones, Reutzel, and Clark () describe just such a multicomponential alphabet knowledge lesson format that requires only about 12 minutes per day to teach, as shown in Figure .…”
Section: Alphabet Letter Names and Sounds “Rn't” So Easy To Learnmentioning
confidence: 99%
“…Finally, although not yet rigorously evaluated, correlational evidence suggests that children may benefit from learning lowercase letter forms in conjunction with or subsequent to learning uppercase forms (e.g., teaching b after children have already learned B ; Bowles, Piasta, & Musielak, 2013 ;Pence Turnbull et al, 2010 ). Indeed, although other recommended alphabet instructional practices are aligned with research (see IRA/NAEYC;Jones, Clark, & Reutzel, 2013 , for review), few have been empirically evaluated, and more work is needed in this area (Phillips & Piasta, 2013 ;Piasta & Wagner, 2010a ).…”
Section: Assessment Instructionmentioning
confidence: 99%